Modelo predictivo para determinación de homicidios intencionales en Ecuador, 2020 - 2024 - Sarmiento Fajardo, Manuel Fabrizzio (2025)
This research addresses the escalation of intentional homicides in Ecuador (2020-2024) using a time-series forecasting approach. The study transforms individual incident data into monthly time series representing four key patterns: total case volume, predominant weapon type, sociodemographic profile of victims, and geographic concentration. A comparative evaluation framework of three predictive models Prophet, SARIMA, and Holt-Winters is then developed to select the most accurate algorithm for each pattern. The main output is a five-year projection (2025-2029) that suggests the chronicity of the crisis at historically high levels, offering a quantitative and data-driven perspective on the future trajectory of the phenomenon.